Comparison of cardiovascular disease risk association with metabolic unhealthy obesity identified by body fat percentage and body mass index: Results from the 1999–2020 National Health and Nutrition Examination Survey - Xiong, Qian; Zhang, Yang; Li, Jun; An, Yaping; Yu, Shan (PloS one, 2024)
Cardiovascular disease (CVD) risk among individuals across different categories of metabolic obesity phenotypes is controversial. The study used body fat percentage (BFP) or body mass index (BMI) to categorize obese status and to investigate the association between metabolic obesity phenotypes and CVD risk in a nationally representative population. This cross-sectional study included 49463 adult participants in National Health and Nutrition Examination Survey from 1999 to 2020. Metabolic healthy status was defined by the absence of metabolic syndrome according to the revised National Cholesterol Education Program Adult Treatment Group definition. Obesity was identified by BFP, assessed by dual-energy X-ray absorptiometry scan, and BMI. The primary outcome was CVD prevalence. The multivariable logistic regression model and restricted cubic spline analyses were used to examine the associations between metabolic obesity phenotypes and the risk of CVD. Among 49463 adult participants, 32.12% were metabolically unhealthy, 34.10% were overweight, 37.94% were obese; and 8.41% had CVD. Compared with metabolic healthy normal weight, metabolic healthy obesity, and metabolic unhealthy normal weight/overweight/obesity were all associated with increased CVD risk with adjusted odds ratios (95% confidence intervals) of 1.45 (1.14-1.85), 2.80(1.53-5.11), 2.55(1.88-3.47), and 2.96(2.18-4.02), respectively. Nonlinear dose-response relationships between BFP and CVD were observed both in metabolically healthy and unhealthy participants (both P for non-linearity<0.0001). When obesity was defined with BMI, there were a similar prevalence of obesity, and similar associations between metabolic obesity phenotypes and CKD risks. Metabolic healthy and unhealthy obesity were both associated with higher risks of CVD, whether using BFP or BMI to define obese status. It suggests that metabolic obesity phenotype is a risk factor for CVD.